SARS-COV-2 myocarditis in a high school athlete after COVID-19 and its implications for clearance for sports - Das, B. B. (Children, 2021)
This case report describes a high school athlete with palpitation, myalgia, fatigue, and dyspnea on exertion after SARS-CoV-2 infection with evidence of myocarditis by cardiac magnetic resonance (CMR), but echocardiography and troponin were normal. This case is unusual as the standard cardiac tests recommended by the American Heart Association for sports clearance, including ECG, echocardiography, and cardiac biomarkers, were normal. Still, she continued to be symptomatic after mild COVID-19. The CMR was performed to evaluate her unexplained palpitation and showed patchy myocardial edema two months after her initial SARS-CoV-2 infection. In this case, the diagnosis of myocardial involvement would be missed by normal echocardiograms and cardiac bio-markers without CMR. Because acute myocarditis is a risk factor for sudden death in competitive athletes, pediatric cardiologists should consider performing additional tests such as cardiac MRI in symptomatic COVID-19 patients, even if cardiac biomarkers and echocardiograms are normal.